The Concentration of Micronutrients and Heavy Metals in Maternal Serum, Placenta, and Cord Blood: A Cross-Sectional Study in Preterm Birth - Rima Irwinda; Noroyono Wibowo; Atikah Sayogo Putri (Journal of Pregnancy)
Background. Preterm birth is still a global burden particularly in Indonesia. The suboptimal concentration of certain micronutrients and heavy metals is hypothesized to play a role in the mechanism of preterm birth. Objective. This study aimed to analyze the micronutrients and heavy metals concentrations between subjects with term and preterm birth. Design. A cross-sectional study was conducted during January–June 2017 in Cipto Mangunkusumo Hospital and Budi Kemuliaan Hospital, Jakarta, Indonesia. Subjects were divided into term and preterm birth groups. The measured outcomes were maternal serum, placental, and blood cord concentration of zinc, copper, iron, selenium, manganese, mercury, lead, AtRA, and 25(OH)D. Results. A total of 51 pregnant women participated in this study. Term group had higher concentration of maternal serum AtRA (0.22 ± 0.07 ng/mL versus 0.12 ± 0.03 ng/mL, p <0.001), higher placental concentration of manganese {0.99 (0.38 – 1.78) μg/g versus 0.42 ± 0.18 μg/g, p <0.001}, iron (252.16 ± 170.61 μg/g versus 78.45 ± 51.73 μg/g, p <0.001), copper {2.96 ± 1.80 μg/g versus 1.62 (0.70 – 3.88) μg/g, p 0.019}, zinc {58.34 (27.88 – 124.05) μg/g versus 28.41 (1.46 – 137.69) μg/g, p 0.011}, selenium (0.31 ± 0.31 ng/g versus 0.14 ± 0.20 ng/g, p 0.024), AtRA {21.7 ± 10.69 ng/g versus 0.7 (0.42 – 5.10) ng/g, p <0.001}, and 25(OH)D {75.84 ± 45.12 ng/g versus 18.00 (5 – 88) ng/g, p <0.001}, lower placental concentration of mercury (0.20 ± 0.17 ng/g versus 20.47 ± 41.35 ng/g, p 0.019) and lead (0.02 ± 0.01 ng/g versus 0.81 ± 1.43 ng/g, p 0.009), and higher cord blood concentration of copper {32.20 (16.30 – 69.60) μg/dL versus 20.60 (5.80 – 53.30) μg/dL, p 0.006} and AtRA (0.16 ± 0.04 versus 0.07 ± 0.01, p <0.001). Conclusion. Preterm birth is associated with lower concentrations of micronutrients which play a role in antioxidant mechanism, as well as higher concentration of mercury and lead.